PENGGUNAAN GOOGLE FORM SEBAGAI ALAT EVALUASI PEMBELAJARAN PADA MATA PELAJARAN BAHASA INDONESIA : Studi Deskriptif Analitis pada Kelas VIII di Sekolah Menengah Pertama Negeri 1 Lembang - Fauzi, Muhammad Rizal (2014)
Muhammad Rizal Fauzi (0900416). The Use of Google Form as an Evaluation Tool of Learning on Indonesian Language Subject (Study Descriptive Analytical for Eight Grade of Junior High School 1 Lembang ).Thesis of Curriculum and Education Technology Major, Faculty of Education, Indonesian University of Education, by 2013.This study concerns the use of Google Form in activities learning evaluation on indonesian language subject for Eight Grade of Junior High School 1 Lembang. Through the use of Google Form as evaluation tool are expected to provide ease in learning evaluation activities from planning to evaluation of the impact of efficiency, effectiveness, an attraction for teachers and students. This study was conducted to answer the research problems that have been formulated, namely "How to develop a Google Form as an evaluation tool of learning on Indonesian language Subject for Eight Grade of Junior High School 1 Lembang?. This research used study descriptive analytical method and data collection techniques including interviewing, observation, question form, and documentation studies. The population in this study is all eight grade students of junior high school 1 Lembang. The sample in this study is eight-B grade students of junior high school 1 Lembang with technique sampling used purposive random sampling. Based on the general conclusion, results of this research on the use of Google Forms as an evaluation tool of learning on Indonesian Language subjects starting from the planning stage, the readiness of facilities and infrastructure, the development of the Google Form, until the implementation stage the use of Google Forms in the evaluation of learning impact and benefits of both aspects of effective, efficiency, attractiveness and appearance design. For teachers, greatly helped by the existence of a Google Form both in terms of cost, time, and effort. For the students themselves became more interested, enthusiastic, active and not to be a negative thing for the exams in junior high school 1 Lembang Keywords: Google Form, Evaluation Tool of Learning Muhammad Rizal Fauzi (0900416). Penggunaan Google Form Sebagai Alat Evaluasi Pembelajaran pada Mata Pelajaran Bahasa Indonesia (Studi Deskriptif Analitis pada Kelas VIII di Sekolah Menengah Pertama Negeri 1 Lembang ). Skripsi Jurusan Kurikulum dan Teknologi Pendidikan, Fakultas Ilmu Pendidikan, Universitas Pendidikan Indonesia, Tahun 2013. Penelitian ini menyangkut penggunaan Google Form dalam kegiatan evaluasi pembelajaran pada mata pelajaran Bahasa Indonesia kelas VIII di SMP Negeri 1 Lembang. Melalui penggunaan alat evaluasi Google Form diharapkan mampu memberikan kemudahan dalam kegiatan evaluasi pembelajaran baik dari perencanaan evaluasi sampai kepada dampak efesiensi, keefektifan, daya tarik bagi guru dan siswa. Penelitian ini dilakukan untuk menjawab masalah-masalah penelitian yang telah dirumuskan, yaitu "Bagaimana mengembangkan Google Form sebagai alat evaluasi pembelajaran pada mata pelajaran Bahasa Indonesia terhadap kelas VIII di SMP Negeri 1 Lembang ?. Penelitian ini menggunakan metode deskriptif analitis dengan teknik pengumpulan data berupa pedoman wawancara, observasi, angket, dan studi dokumentasi. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 1 Lembang. Sampel yang digunakan adalah kelas VIII-B SMP Negeri 1 Lembang dengan teknik pengambilan sampel menggunakan purposive random sampling. Berdasarkan kesimpulan umum, hasil penelitian mengenai penggunaan Google Form sebagai alat evaluasi pembelajaran pada mata pelajaran Bahasa Indonesia dimulai dari tahap perencanaan, kesiapan sarana dan prasarana, pengembangan Google Form, sampai kepada tahap implementasi penggunaan Google Form dalam kegiatan evaluasi pembelajaran memberikan dampak dan manfaat baik dari aspek efektif, efesiensi, daya tarik dan desain tampilan. Bagi guru, sangat terbantu dengan adanya Google Form baik dari segi biaya, waktu, dan tenaga. Bagi siswa sendiri menjadi lebih tertarik, antusias, aktif dan tidak menjadi hal yang negatif untuk menghadapi ujian di SMP Negeri 1 Lembang. Kata Kunci : Google Form, Alat Evaluasi Pembelajaran